Market-driven Plant Breeding for Practicing Breeders - Tiwari, Aparna; Tikoo, Surinder K.; Angadi, Sharan P.; Kadaru, Suresh B.; Ajanahalli, Sadananda R.; MJ Vasudeva Rao (Springer, 2023)
This book highlights the technicalities of plant breeding in a seed-business environment and explains the crucial aspects of the value chain. It educates the readers on how to initiate, participate, sustain national and international agreements for material transfer, how consortia work to facilitate germplasm accessibility, and how to set visionary goals to develop a superior plant varieties. The book covers the aspects such as how to conduct disease screening trials at hot spots, preparing an operational budget, and how to accelerate product advancement. Plant breeding is broadly defined as manipulation of plant genotypes to create phenotypes that are beneficial to mankind. It helps to achieve food security and sustainability by developing high yielding, climate-resilient, nutritious varieties of crops and hence is able to address unprecedented challenges like rising global population, diminishing genetic biodiversity, and uncertainties of the weather . This book is an extraordinary source of information starting from goal-genesis to market-oriented product-profiling and help readers to accelerate/enhance? their work/professional performance more effectively. This book will be very useful to practicing plant breeders at various levels in the public and private sectors. It is a must-have book for potential plant breeders who enter plant breeding profession just after the completion of their formal plant breeding education.